Publisher Correction: Robust prediction of response to immune checkpoint blockade therapy in metastatic melanoma. (December 2018) - Auslander, Noam; Zhang, Gao; Lee, Joo; Frederick, Dennie; Miao, Benchun; Moll, Tabea; Tian, Tian; Wei, Zhi; Madan, Sanna; Sullivan, Ryan; Boland, Genevieve; Flaherty, Keith; et al.
In the version of this article originally published, there was an error in the URL linked to by an accession code in the data availability section of the methods. The erroneous URL was:https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE100351 . The correct URL is:https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE115821 . The error has been corrected in the HTML and PDF versions of this article.